2006
DOI: 10.1007/s10597-006-9069-0
|View full text |Cite
|
Sign up to set email alerts
|

Severely Mentally Ill Women’s HIV Risk: The Influence of Social Support, Substance Use, and Contextual Risk Factors

Abstract: In structured interviews with 96 women with severe mental illness, nearly two-thirds had not used condoms during sexual intercourse in the past 3 months, more than two-thirds had sex with multiple partners, and almost one-third had been treated for a sexually transmitted infection (STI) in the past year. Women who reported fewer sexual risk context factors, such as having sex with someone the participant did not know or transactional sex, had fewer sexual partners. Larger social support networks were associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Finally, while cigarette smoking was associated with unprotected sex among both genders, sex under the influence of alcohol or drugs, and having suffered any verbal violence were independent correlates of unprotected sex among women only, and this result was consistent with other studies 26,27,28,29,30,31 . Sex under the influence of alcohol or drugs can alter cognitive abilities and decision-making power, thus potentially leading to high risk behaviors 6 .…”
Section: Discussionsupporting
confidence: 90%
“…Finally, while cigarette smoking was associated with unprotected sex among both genders, sex under the influence of alcohol or drugs, and having suffered any verbal violence were independent correlates of unprotected sex among women only, and this result was consistent with other studies 26,27,28,29,30,31 . Sex under the influence of alcohol or drugs can alter cognitive abilities and decision-making power, thus potentially leading to high risk behaviors 6 .…”
Section: Discussionsupporting
confidence: 90%
“…Gordon et al [16] found that adults with SMI were often unable to communicate effectively about safer sex with their partners. Difficulties in interpersonal interactions may lead to a lack of social support, which has been associated with having unprotected sex, both directly and indirectly through sex after drug use [12,19]. Individuals with SMI have lower sexual risk-reduction self-efficacy than individuals without SMI [20]; in turn, a lack of assertiveness skills and lower sexual riskreduction self-efficacy have been associated with HIV risk behavior among individuals with SMI [11].…”
Section: Sexual Risk Behavior Among Individuals With Severe Mental Ilmentioning
confidence: 99%
“…An average of more than 60% of the people with SMI correctly answered the questionnaire evaluating knowledge about HIV/AIDS (Guimarães, McKinnon, Campos, Melo & Wainberg, 2010;Knox, Boaz, Friedrich & Dow, 1994;Magagula, Mamabolo, Krüger & Fletcher, 2012;Otto-Salaj, Heckman, Stevenson & Kelly, 1998;Randolph et al, 2007;Stevenson & Eilers, 1992;Strauss, Bosworth, Stechuchak, Meador & Butterfield, 2006;Wainberg et al, 2008).…”
Section: Knowledge and Beliefs About Hiv/aidsmentioning
confidence: 99%
“…Prevalence of sexual abuse of people with SMI varies between 14% and 40% Coverdale et al, 1994;Coverdale et al, 2000;Randolph et al, 2007). Besides the inherent risk in sexual abuse that the perpetrators may be infected, studies made with United States adults and adolescents report that sexual abuse during the childhood of people with SMI is associated with a greater number of risky sexual practices and a greater probability of substance use (Brown, Houck, Hadley & Lescano, 2005;Brown, Lourie, Zlotnick & Cohn, 2000;Dévieux et al, 2007).…”
Section: Gender Inequality and Vulnerabilitymentioning
confidence: 99%